Advances in peptide-drug conjugate-based supramolecular hydrogel systems for local drug delivery - Qi Shang; Yun Su; Faith Leslie; Mingjiao Sun; Feihu Wang (Medicine in Drug Discovery, 2022)
Peptide-drug conjugate (PDC) systems consisting of peptide, linker and drug, have attracted extensive attention in drug delivery applications. With the assistance of peptides, the PDC systems have competitive advantages over other drug delivery vehicles, with excellent biocompatibility, easy accessibility, biodegradability, and multifunctionality. Through self-assembly or stimuli-instructed assembly processes, the PDC system is capable of creating supramolecular hydrogel scaffolds with discrete filamentous nanostructures that undergo subsequent elongation and supramolecular network entanglements to form a macroscopic hydrogel. Notably, the hydrogel can serve as a prospective localized delivery platform for concentrating the drug in the target site, thus improving the drug bioactivity and attenuating the off-target toxicity. Additionally, the incorporation of peptide-containing targeting or bioactive elements can enhance the hydrogel’s multifunctionality, facilitating drug penetration in the deep disease tissue or exerting therapeutic effect. In this review, we will summarize recent research on PDC-based supramolecular hydrogels for localized drug delivery, as well as briefly discuss the challenges and prospects for clinical applications.